Hubungan Self-Disclosure dan Trust pada Individu yang Menjalin Hubungan Romantis Daring - Wilda Nidia Maharani; Nur Eva (Flourishing Journal, 2026)
Advances in digital technology have transformed the ways in which individuals form and maintain romantic relationships, particularly through online platforms that reduce the intensity of face-to-face interactions and the exchange of nonverbal cues. This situation positions self-disclosure as a crucial variable in the process of building trust between partners. This study was designed to examine the correlation between self-disclosure and trust among individuals in online romantic relationships. The study employed a quantitative, correlational design involving 104 young adult participants currently in online romantic relationships. Data were collected via an online questionnaire using validated scales for self-disclosure and trust. Data analysis procedures included descriptive statistics, assumption testing, and Pearson’s correlation test. The results revealed a significant positive correlation between self-disclosure and trust, indicating that individuals with a higher capacity for self-disclosure tend to exhibit higher levels of trust toward their partners. These findings reinforce the role of self-disclosure as a fundamental psychological mechanism in the formation and maintenance of trust in online romantic relationships, while also providing an empirical contribution to the development of research on the psychology of interpersonal relationships in the digital age. Abstrak Kemajuan teknologi digital telah mentransformasi pola individu dalam membangun serta memelihara relasi romantis, utamanya melalui platform daring yang mereduksi intensitas interaksi langsung maupun pertukaran isyarat nonverbal. Kondisi tersebut menempatkan keterbukaan diri (self-disclosure) sebagai variabel krusial dalam proses terbentuknya kepercayaan (trust) di antara pasangan. Penelitian ini dirancang untuk mengkaji korelasi antara self-disclosure dan trust pada individu yang menjalin ikatan romantis secara daring. Studi ini menggunakan pendekatan kuantitatif berdesain korelasional dengan melibatkan 104 partisipan dewasa muda yang tengah menjalani hubungan romantis berbasis daring. Pengumpulan data dilaksanakan melalui instrumen kuesioner daring dengan menggunakan skala self-disclosure dan trust yang telah teruji reliabilitasnya. Prosedur analisis data mencakup statistik deskriptif, pengujian asumsi, serta uji korelasi Pearson. Hasil penelitian mengungkapkan terdapatnya korelasi positif yang signifikan antara self-disclosure dan trust, yang menunjukkan bahwa individu dengan kapasitas keterbukaan diri yang lebih tinggi memiliki kecenderungan untuk menampilkan tingkat kepercayaan yang lebih tinggi terhadap pasangannya. Temuan tersebut mengukuhkan kedudukan self-disclosure sebagai mekanisme psikologis yang fundamental dalam pembentukan dan pemeliharaan trust pada relasi romantis daring, sekaligus memberikan sumbangan empiris bagi pengembangan kajian psikologi relasi interpersonal di era digital.